Poetic transmutation of data in “R-Scuti – when the stars play” (2019) - Camargo, Gabriel Cesar; Paraguai, Luisa (DAT Journal, 2024)
Based on the installation work “R-Scuti – when the stars play” (2019) by the Realidades group (ECA/USP), the aim is to address the visualisation of data as sound and sound narratives that articulate light and sound frequencies in images. Using astronomical data from the star R-Scuti, the artistic proposal transforms the star’s memory of light into sound frequencies, reproduced in a structure with water, generating visual patterns (Laurentiz, 2019). The different materialities of data representation (Khan e Shah, 2011; Manovich, 2004; Manovich, 2011; Venturelli e Melo, 2019) permeate different perceptive modalities, and in this sense, the poetic exercise formalises relationships between intersigns.